2015
DOI: 10.7860/jcdr/2015/12705.6202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Caries Removal Using Polymer Bur, Stainless Steel Bur, Carisolv, Papacarie – An Invitro Comparative Study

Abstract: The Mean time taken by Stainless Steel Bur excavation was found to be less and caused more amount of dentinal tubule destruction when compared to Polymer Bur, Carisolv and Papacarie. Chemo-mechanical methods found to be more efficient with lesser amount of bacterial remnants and dentinal tubule destruction after caries excavation when compared to conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
6
22
0
2
Order By: Relevance
“…Aswathi et al 11 found the same results of polymer burs being more efficient in reducing the total viable count. Similar results were also shown by Divya et al 12 in their comparative study on efficacy of caries removal using polymer bur, conventional bur, Carisolv and Papacarie with The time required for removal of caries with smart bur removal method took an average of 147.5 seconds when compared to conventional bur, which took only 79.3 resulting in a statistically significant difference between both the groups (p value = 0.001). The possible reason would be the higher hardness number (7,000 KHN) and higher cutting efficiency of the diamond bur.…”
Section: Discussionsupporting
confidence: 84%
“…Aswathi et al 11 found the same results of polymer burs being more efficient in reducing the total viable count. Similar results were also shown by Divya et al 12 in their comparative study on efficacy of caries removal using polymer bur, conventional bur, Carisolv and Papacarie with The time required for removal of caries with smart bur removal method took an average of 147.5 seconds when compared to conventional bur, which took only 79.3 resulting in a statistically significant difference between both the groups (p value = 0.001). The possible reason would be the higher hardness number (7,000 KHN) and higher cutting efficiency of the diamond bur.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, minimal invasive caries removal treatment is of great importance in dental care for children. In addition, the concept of preserving sound dentine in the Chemomechanical caries removal (CMCR) method is of great interest among dental researchers and patients. Chemomechanical caries removal (CMCR) is a non‐invasive intervention that removes decayed dentine, preserves sound dental tissues, and avoids pulp annoyance and patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional methods involve the use of rotary burs, alone or together with metal hand instruments. 7 The pain and discomfort associated to conventional cavity preparation have lead to the reluctance of many patients to seek dental treatment. 19 Besides this, the local anaesthesia, frequently needed to control the pain associated with cavity preparation, is potentially responsible for discomfort and pain.…”
Section: Discussionmentioning
confidence: 99%